Multispecies probiotics applications through feed addition on cultured tilapia to prevent streptococcosis - Nurin Dalilah Ayu Destianingrum; Munti Yuhana; Angela Mariana Lusiastuti (Jurnal Akuakultur Indonesia)
ABSTRACT